Encyclopedia of Analytical Chemistry 2000
DOI: 10.1002/9780470027318.a5206
|View full text |Cite
|
Sign up to set email alerts
|

Second‐Order Calibration and Higher

Abstract: Most analytical chemists recognize calibration as the quantitation of analytes by relating the analyte signal and analyte concentration, although it is also possible to obtain information about other characteristics of the sample through calibration. In the calibration process, a number of samples that have known values of the characteristic to be determined, e.g. concentration, are measured. These are reference measurements, and are known as calibration standards. Traditionally, the measurements have consiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…Moreover, the proposed algorithm can overcome the slow convergence brought about by random initialization or high multicollinearity to some extent. In other words, the APTLD algorithm has a much higher convergence rate compared with the traditional PARAFAC algorithm [37][38]. The results of treating one simulated and one real excitation-emission spectral data set showed that the proposed algorithm performs well.…”
Section: Introductionmentioning
confidence: 73%
“…Moreover, the proposed algorithm can overcome the slow convergence brought about by random initialization or high multicollinearity to some extent. In other words, the APTLD algorithm has a much higher convergence rate compared with the traditional PARAFAC algorithm [37][38]. The results of treating one simulated and one real excitation-emission spectral data set showed that the proposed algorithm performs well.…”
Section: Introductionmentioning
confidence: 73%
“…In addition, selecting diagonal elements makes ATLD retain trilinearity property indeed and be insensitive to the excessive estimation of component numbers. The advantages have been reviewed by Fleming and Kowalski [16]. Based on the above advantages, it is very suitable to handle second-order data obtained from hyphenated instruments, such as HPLC-DAD, LC-MS, and GC-MS.…”
Section: Atldmentioning
confidence: 99%
“…The parallel factor analysis (PARAFAC) /canonical decomposition (CANDECOMP) model is a classical three‐way component model in chemometrics . With the development of second‐order calibration based on PARAFAC/CANDECOMP model, scientists found that the model can provide excellent selectivity even in the case when unknown interference exists . This feature has been recognized as “second‐order advantage” .…”
Section: Introductionmentioning
confidence: 99%